Doctors' views on diabetes. Issue 6 (June 1984) - Marteau, T M; Baum, J D
Abstract : Children with diabetes may be managed by either paediatricians or adult physicians with a particular interest in diabetes. This study compares the views of these two groups of doctors on juvenile onset diabetes. A questionnaire was given to all doctors attending two conferences, one primarily for paediatricians and one primarily for adult physicians with a particular interest in diabetes. Adult physicians estimated morbidity and mortality from juvenile onset diabetes to be significantly higher after 30 years than did paediatricians. The two groups of doctors also differed in the target blood glucose concentrations they considered optimal for diabetic children–more paediatricians opted for higher values than did adult physicians. The findings of this study support the view that paediatricians and adult physicians view juvenile onset diabetes differently. The origin of these differences is uncertain but may relate to the contrasting clinical experiences of the two groups of specialists.